Efficacy of green tea-based mouthwashes on dental plaque and gingival inflammation: A systematic review and meta-analysis - Ankita Mathur; D Gopalakrishnan; Vini Mehta; S A Rizwan; Sahana Hegde Shetiya; Shreya Bagwe (Wolters Kluwer Medknow Publications, 2018)
Objectives: The purpose of this study was to conduct a systematic review and if appropriate a meta-analysis of the efficacy of daily rinsing with green tea-based mouthwashes in terms of plaque index (PI) and/or gingival index (GI) as compared to other mouthwashes in plaque-induced gingivitis patients. Materials and Methods: MEDLINE, Cochrane Central Register of Controlled Trials, IndMed, Google Scholar, and major journals were searched for studies up to December 2016. A comprehensive search strategy was designed, and the eligible articles were independently screened for eligibility by two reviewers. Randomized controlled trials in which individuals were intervened with oral mouthwashes of interest were included. Where appropriate, a meta-analysis was performed and standardized mean differences (SMDs) for GI and PI were calculated. Results: A total of 9 articles out of the 311 titles met the eligibility criteria. A meta-analysis was performed for five studies that compared green tea-based mouthwashes with chlorhexidine (CHX). The SMD for PI was −0.14 (95% CI: −1.70, 1.43; P = 0.86 and I2 = 94%), while that for GI was 0.43 ((95% CI: -0.63, 1.49; P = 0.43, I2 = 89%). Both these estimates suffered from significant heterogeneity. For both PI and GI, two studies were in favor of green tea while three studies were in favor of CHX. Conclusions: Green tea-based mouthwashes can be considered an alternative to CHX mouthwashes in sustaining oral hygiene, especially because of the added advantages provided by such herbal preparations.